2019
DOI: 10.1002/ange.201903323
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Hierarchical Porosity in Metal–Organic Frameworks by the Modulation of Cation Valence

Abstract: Hierarchically porous metal–organic frameworks (HP‐MOFs) have attracted great attention owing to their advantages over microporous MOFs in some applications. Despite many attempts, the development of a facile approach to generate HP‐MOFs remains a challenge. Herein we develop a new strategy, namely the modulation of cation valence, to create hierarchical porosity in MOFs. Some of the CuII metal nodes in MOFs can be transformed into CuI via reducing vapor treatment (RVT), which partially changes the coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…[9b] The rapid N 2 uptake at low P/P 0 interval indicates the microporosity. [17] The Brunauer-Emmett-Teller (BET) surface area is estimated to be 294.0 m 2 • g À 1 . The pore size distributions (Figure 5b) derived from the adsorption branch of the isotherm utilizing the Barrett-Joyner-Halenda (BJH) model showed that it had micropores at a peak of 1.7 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[9b] The rapid N 2 uptake at low P/P 0 interval indicates the microporosity. [17] The Brunauer-Emmett-Teller (BET) surface area is estimated to be 294.0 m 2 • g À 1 . The pore size distributions (Figure 5b) derived from the adsorption branch of the isotherm utilizing the Barrett-Joyner-Halenda (BJH) model showed that it had micropores at a peak of 1.7 nm.…”
Section: Resultsmentioning
confidence: 99%
“…2c. 62 Their experiments showed that a portion of the Cu II sites was reduced to Cu I by the CH 3 OH vapor, which destroys some of the coordination bonds, resulting in the formation of mesopores in the microporous framework and the formation of macropores. Moreover, Song et al used hydroquinone (H 2 Q) to reduce Cu 2+ ions in HKUST-1 for the first time to obtain mesopores.…”
Section: Mesopore Scalementioning
confidence: 99%
“…The first category includes the use of elongated ligands 15 , 16 , metal-ligand-fragment co-assembly 17 , 18 , and imperfect crystallization 19 , 20 methods. The second category comprises the use of sacrificial soft or hard templates 21 23 , modulator-induced defect formation 24 , cation valence modulation 25 , and ligand exchange 26 . All of these methods, however, suffer from their limited applicability (i.e., only a few MOF structures or ligand types are suitable), a lack of control over shape, location, and spatial distribution of the introduced porosity, and an undesired loss of crystallinity, often accompanied by considerable pore collapse upon synthesis or post-processing.…”
Section: Introductionmentioning
confidence: 99%